Efektivitas PLP Link and Match dengan Profil Lulusan Prodi MPI UIN Sunan Kalijaga - Afiq Fikri Almas; Misbah Ulmunir (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2017)
The regulation of the Director General of Islamic Education No. 1429 year 2012 dated August 31, 2012 on the Arrangement of Study Program in Islamic Higher Education required the Department of Islamic Education (KI) to change its name to Islamic Education Management (MPI) Study Program which inevitably resulted in the adjustment of its graduates profile as well as its curriculum. As a consequence, this has raised some problems in terms of the implementation of the -commonly applied- professional training program. This is a qualitative research applying interviews, field notes, and documentation as its data collection methods. Sample in this research was determined by non-probability sampling and snowball sampling techniques. The result of the research shows the effectiveness of the professional training program-link and match- with the graduate profile of MPI UIN Sunan Kalijaga Yogyakarta.